Retirement Benefits in the Chile an Social Security System - Niżnik, Joanna (Studia Oeconomica Posnaniensia, 2013)
The aim of this paper is to present the principles underpinning the system of retirement products and public benefits in Chile in the context of the government's efforts to reduce poverty among the elderly and improve the financial situation of this group. The first part outlines the overall structure of the pension system, paying particular attention to the principles behind the creation of pension funds and the forms of pension pay-outs. The second part focuses on the major factors that led to pension reform in 2008 as well as the changes to the pension system which were designed to reduce the level of poverty among pensioners, expand the social insurance obligation, and increase the value of retirement benefits.